A COMPARATIVE QUALITATIVE STUDY OF DISPERSIBLE TABLETS OF THREE DIFFERENT COMMERCIAL BRANDS - Kishore, Ankita; Kashyap, Pradeep; Sharma, Devender; Singh, Ranjan Kumar (Journal of Biomedical and Pharmaceutical Research, 2019)
Dispersible tablets are uncoated or film-coated tablets meant to be spread in water before administration giving a unvaried dispersion. Pediatric and old patients face complications in swallowing the conventional tablets. So according to the need dispersible tablets have been developed which combine the benefits of liquid dosage forms and solid dosage forms. The dispersible tablets allow dispersion in water prior to administration. In present study we have compared three brands of different dispersible tablets. The objective of the study was to find out the best dosage form based on the post compression parameters of dispersible tablets and to develop a co-relation among these parameters. Three brands of dispersible tablets had been selected i.e. Acetylsalicylic acid, Cefixime & Paracetamol tablets and they have been compared on the basis of different parameters of dispersible tablets like uniformity of weight, friability testing, hardness, wetting time, wetting volume, water absorption ratio, dispersion time, disintegration time, uniformity of dispersion. Acetylsalicylic acid & Cefixime complies all the parameters except friability test, while Paracetamol tablets complies all the tests except it was showing more hardness compared to other two brands due to which it’s properties like wetting time, wetting volume, water absorption ratio, dispersion time, disintegration time was lower than other two. So after overall comparison Cefixime was found to be the best in comparison to other two brands.Keywords: Dispersible tablets, paracetamol, cefixime, acetylsalicylic acid, comparison, post compression parameters.